Brachial artery access for transcatheter aortic valve implantation - Topalo, Robert; Hájek, Petr; Vik, Karel; Adlová, Radka; Horn, Milan; Veselka, Josef (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
We describe a case of an 80-year-old male patient with symptomatic severe aortic stenosis treated with transcatheter valve implantation (TAVI). The most common and preferred type of transcatheter valve delivery is through the femoral artery. However, if transfemoral access is not possible, an alternate route may be chosen. Such routes include, but are not limited to, direct aortic access, subclavian/axillary access, or transapical access, each one having their advantages and disadvantages [1, 2]. In our patient, transfemoral access was not possible due to extreme tortuosity of both pelvic arteries revealed on preoperative angiography. Computed tomography (CT) angiography was used to assess the diameter of the subclavian, axillary and brachial arteries (Figures 1 A, B). Duplex ultrasound verified the proximal diameter of the right brachial artery to be 6.7 mm (Figure 1 C). This diameter was sufficient to perform TAVI with an Evolut R 34 mm valve via the brachial artery. This approach offers multiple benefits, primarily, relatively easy access, avoidance of preparation of an artery in the otherwise very complex axillary and subclavian region, therefore decreasing chances of iatrogenic injury, and a quick recovery after the procedure. Other benefits of transbrachial delivery are usually minimal tortuosity of the arterial segment and minimal calcification. A major limitation of this approach is the diameter of the brachial artery. Other disadvantages are the same as for subclavian/axillary access and involve the angle of the aorta from the horizontal plane, as well as the unfavorable angle of valve delivery into the left ventricular outflow tract.